High protein Chinese steamed bread : physico-chemical, microstructural characteristics and gastro-small intestinal starch digestion in vitro : a thesis presented in partial fulfilment of the requirements for the degree of Master of Food Technology at Massey University, Manawatū, New Zealand - Mao, Shiyuan (Massey University, 2019)
In Asia, high protein low carbohydrate foods are in high demand because their consumption can provide improved nutritional benefits and help maintaining blood glucose levels close to normal. High protein versions of popular, highly consumed food products (staple foods) such as Chinese steamed bread (CSB) can be very useful to improve the health status of our populations. Thus, the objectives of this study were: to develop high protein Chinese steamed bread (HPCSB) using plant protein, dairy protein combinations. The high protein versions of the steamed breads were then compared with control 100% wheat flour based Chinese steamed bread for physico-chemical, microstructural, textural and in vitro starch digestion characteristics. In order to develop HPCSB, plant proteins (soy protein isolate) and dairy proteins (rennet casein and milk protein concentrate) were blended into wheat flour at two different levels. The addition of proteins has led to a change in colour characteristics (L*, a*, b*) and also resulted in a decreased specific volume of the breads. The textural characteristics measured through textural profile analysis of HPCSB showed an increased hardness and gumminess than control. The microstructure of HPCSB was observed to be more compact and had fewer air cells when observed through Scanning Electronic Microscopy. Furthermore, in vitro starch digestion of HPCSB depicted that the addition of proteins was capable of lowering the starch hydrolysis (%) and estimated glycaemic index (eGI), especially for RC I and RC II at significant levels. Addition of both proteins influenced the microstructure of HPCSBs, which in turn affected the textural and starch digestion properties. High protein Chinese steamed bread with low glycaemic properties can be prepared by critically selecting the protein sources with minimum changes in their physical and textural characteristics.
Figures 2.5 (=Kortei et al., 2015 Fig 1) & 2.7 (=Guerra et al., 2012 Fig 1) were removed for copyright reasons.
Keywords: Bread; China; Steaming (Cooking); Plant proteins; Milk proteins; Proteins in human nutrition